Transcriptomic Signatures for Ovulation in Vertebrates - Liu, Dongteng (Gen Comp Endocrinol, 2017)
The central roles of luteinizing hormone (LH), progestin and their receptors for initiating ovulation have been well established. However, signaling pathways and downstream targets such as proteases that are essential for the rupture of follicular cells are still unclear. Recently, we found anovulation in nuclear progestin receptor (Pgr) knockout (Pgr-KO) zebrafish, which offers a new model for examining genes and pathways that are important for ovulation and fertility. In this study, we examined expression of all transcripts using RNA-Seq in preovulatory follicular cells collected following the final oocyte maturation, but prior to ovulation, from wild-type (WT) or Pgr-KO fish. Differential expression analysis revealed 3,567 genes significantly differentially expressed between WT and Pgr-KO fish (fold change ≥2, p<0.05). Among those, 1,543 gene transcripts were significantly more expressed, while 2,024 genes were significantly less expressed, in WT than those in Pgr-KO. We then retrieved and compared transcriptional data from online databases and further identified 661 conserved genes in fish, mice, and humans that showed similar levels of high (283 genes) or low (387) expression in animals that were ovulating compared to those with no ovulation. For the first time, ovulatory genes and their involved biological processes and pathways were also visualized using Enrichment Map and Cytoscape. Intriguingly, enrichment analysis indicated that the genes with higher expression were involved in multiple ovulatory pathways and processes such as inflammatory response, angiogenesis, cytokine production, cell migration, chemotaxis, MAPK, focal adhesion, and cytoskeleton reorganization. In contrast, the genes with lower expression were mainly involved in DNA replication, DNA repair, DNA methylation, RNA processing, telomere maintenance, spindle assembling, nuclear acid transport, catabolic processes, and nuclear and cell division. Our results indicate that a large set of genes (>3,000) is differentially regulated in the follicular cells in zebrafish prior to ovulation, terminating programs such as growth and proliferation, and beginning processes including the inflammatory response and apoptosis. Further studies are required to establish relationships among these genes and an ovulatory circuit in the zebrafish model.